The Influence of P2P, TPF and Size on the Profitability of Rural Banks - Rizki Amelia Cahyaningrum; Indraswari, Citra Rahayu (Contemporary Studies in Economic, Finance and Banking, 2025)
Rural Banks play a vital role in supporting the Indonesian economy by providing credit to MSMEs and rural communities. However, the emergence of financial technology, particularly peer-to-peer (P2P) lending, presents challenges to the profitability and competitiveness of BPRs. This study aims to analyze the impact of P2P lending loan volume, Third Party Funds (DPK), and bank size on the profitability of Rural Banks, as measured by net income, during the 2022–2024 period. Using an associative quantitative approach and purposive sampling, the sample includes the largest-asset ural Bank in each of Indonesia’s 34 provinces. The study employs panel data, combining time series and cross-sectional data. The results show that DPK and bank size have a positive effect on profitability, while P2P lending has no significant impact.